2001
DOI: 10.1161/hh2301.100349
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Cardiac K + Channel Function in Mice

Abstract: Abstract-In the mammalian myocardium, potassium (K ϩ ) channels control resting potentials, action potential waveforms, automaticity, and refractory periods and, in most cardiac cells, multiple types of K ϩ channels that subserve these functions are expressed. Molecular cloning has revealed the presence of a large number of K ϩ channel pore forming (␣) and accessory (␤) subunits in the heart, and considerable progress has been made recently in defining the relationships between expressed K ϩ channel subunits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(97 citation statements)
references
References 140 publications
(228 reference statements)
4
91
1
1
Order By: Relevance
“…In these cells, one can take advantage of the versatility of recent genetic engineering technology [1] and also of the accuracy of single-cell measurement techniques such as patch-clamp and Ca 2+ imaging. So far, molecular mechanisms of fundamental heart functions, such as excitation-contraction coupling, action potential shaping, and β-adrenergic signaling, have been successfully unveiled by using single heart cells of mouse models [2][3][4][5][6][7]. Moreover, these cells also provide a convenient platform for analyzing pathogenic mechanisms and the pathophysiology of hereditary heart diseases in molecular detail [8,9].…”
mentioning
confidence: 99%
“…In these cells, one can take advantage of the versatility of recent genetic engineering technology [1] and also of the accuracy of single-cell measurement techniques such as patch-clamp and Ca 2+ imaging. So far, molecular mechanisms of fundamental heart functions, such as excitation-contraction coupling, action potential shaping, and β-adrenergic signaling, have been successfully unveiled by using single heart cells of mouse models [2][3][4][5][6][7]. Moreover, these cells also provide a convenient platform for analyzing pathogenic mechanisms and the pathophysiology of hereditary heart diseases in molecular detail [8,9].…”
mentioning
confidence: 99%
“…Early success in suppressing excitability has involved the targeted expression of modified ion channels or receptors (10,15,16). A promising approach for enhancing electrical activity involves the dominantnegative suppression of K ϩ currents involved in membrane repolarization and excitability (17,18).…”
mentioning
confidence: 99%
“…It has been reported that the cardiac action potentials in mice were lengthened by 10 nmol/L diltiazem, a finding that may be explained by diltiazem-induced blockade of the I to (slow) currents generated by the Kv1.4 channel [33] . The Kv1.4 channel, as the major component of I to (slow), which in turn is a major contributor to phase 1 and the early part of phase 2 of the action potential, plays an important role in the repolarization of the endocardial region of the left ventricle [34] .…”
Section: Discussionmentioning
confidence: 98%